2021
DOI: 10.1111/1471-0528.16936
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of female urinary incontinence: a 4‐year longitudinal study among 24 985 adult women in China

Abstract: Objective To estimate the incidence of urinary incontinence (UI), including its subtypes stress UI (SUI), urgency UI (UUI) and mixed UI (MUI), and to examine risk factors for de novo SUI and UUI in Chinese women. Design Nationwide longitudinal study. Setting Six geographic regions of China. Participants Women aged ≥20 years old were included using a multistage, stratified, cluster sampling method. Methods This study was conducted between May 2014 and March 2016, with follow up in 2018. Data on demographics, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 32 publications
3
22
1
Order By: Relevance
“…The present study confirmed well‐known and widely described risk factors for pregnancy‐related UI, such as advanced age, overweight/obesity, high birth weight, spontaneous tears, episiotomy, and vaginal delivery 22–24 . We also found that employment was a risk factor 25 .…”
Section: Discussionsupporting
confidence: 90%
“…The present study confirmed well‐known and widely described risk factors for pregnancy‐related UI, such as advanced age, overweight/obesity, high birth weight, spontaneous tears, episiotomy, and vaginal delivery 22–24 . We also found that employment was a risk factor 25 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study we included age, self-rated health, and BMI as control variables because of the previous evidence that each was associated with UI [24]. In this study we found that age was a significant predictor of UI, even though our age range was restricted to a 33-year span.…”
Section: Discussionmentioning
confidence: 98%
“…The prevailing view is that the pathophysiology of MUI may involve urethral sphincter deficiency, overactivity of the urethra, detrusor overactivity, or a combination of all three [38]. Increasing age is a wellrecognized risk factor for MUI in many population-based studies, and other risk factors, including delivery, obesity, diabetes, hypertension, hormonal changes, sedentary behaviour, cigarette smoking, chronic medical conditions, and pelvic conditions, could contribute to MUI [46][47][48][49]. This may be related to the underlying pathogenesis of MUI.…”
Section: Discussionmentioning
confidence: 99%